مراقبة التأثيرات الوظيفية لمادة التربية البدنية و الرياضية في الثانوية على المتغيرات القلبية للتلاميذ.(النبض القلبي والضغط الدموي) - حجاج, بومدين (جامعة الوادي - University of Eloued, 2020)
أراد الباحث في هذه الدراسة مراقبة التأثيرات الوظيفية للأنشطة الرياضية الممارسة في حصص التربية البدنية والرياضية على النبض القلبي والضغط الدموي للتلاميذ في الثانوية، و التي تعتبر من أهم المؤشرات على صحة الجسم . خاصة الجهاز القلبي، لأن هذا الجهاز هو أهم الأجهزة في الجسم وله علاقة وطيدة مع اللياقة البدنية. ولا تكون هناك لياقة بدنية إلا إذا كان سليما، ويعمل بطريقة صحيحة. ومعرفة ما إذا كانت لهذه الأنشطة الرياضية فوائد صحية أم لا، وتأثيرات إيجابية على صحة التلميذ الشاب، الذي سيكون رجل الغد، والذي لن يستطيع في المستقبل المساهمة في بناء أسرته، ومجتمعه إلا إذا كان يمتلك جسم بصحة جيدة. محاولا الوصول إلى معرفة تقييمية للأنشطة الرياضية في البرامج المعتمدة في الثانوية، وكشف دورها وتأثيرها على صحة التلاميذ، من الناحية الفيزيولوجية، والتغيرات الوظيفية لأجهزتهم القلبية، والخروج بمقترحات وتوصيات تفيد صحة أبنائنا حول نوع الأنشطة الرياضية المبرمجة، شدتها، وتكرارها داخل المؤسسة التربوية الثانوية. Monitoring the functional effects of physical and physical education in the secondary on the cardiac variables of students (The pulse, and the arterial tension) The researcher studied the effects of physiological or functional of physical education and sports in secondary schools on the body of the student in terms of using his CARDIOVASCULAR, because the heart is one of the most important organs in the human body and its relationship to the physical fitness, and there is no fitness only if it is intact and working in a healthy and correct way. And to see if the sessions of physical activity and sports has health benefits and positive effects on the health of the student or not. Therefore, the researcher divided his study into two parts: 1 - the theoretical side: the researcher explored the theoretical background of the study, which consists of three chapters: 1-1- Chapter I: About physiological cardiovascular system, its definition, its system and its components, and its role in the general functions of the body. 1-2- Chapter II: Education about physical activity sports in the secondary stage, its development, and its role in adolescence when the pupil in the secondary in particular . 1-3 -Chapter III : generals health effects of physiological physical activity and sports on the various organs of the body in adolescence. 2 - field side of the study: Which shows the community of the study, and how to choose the studied sample, and the approach; which is the experimental method, The boundaries of the study the spatial and temporal and The variables of the study. And various procédural and applied stages to the study.
مقال
Keywords: • الفيزيولوجيا ، الجهاز القلبي الوعائي، اللياقة البدنية القلبية، نبض القلب، الضغط الدموي; • Physiology, cardiovascular system, cardiac fitness, heart rate, blood pressure